Identification of bla OXA−51−23−58, bla VIM , bla NDM, and bla IMP carbapenemase genes in Acinetobacter baumannii isolates from hospitalized patients - Kosar Salmani Nasrabadi; Yasaman Ahmadi; Seyed Mahdi Ghasemi; Dariush Shokri (BMC Research Notes)
Abstract Objective The increase of multidrug-resistant (MDR) strains of Acinetobacter baumannii (A. baumannii), especially carbapenem-resistant strains, is challenging for treating infections. This study investigated the antibiotic resistance pattern and frequency of carbapenem resistance genes (oxacillinase and metallo-beta-lactamase) in A. baumannii. Results In this study, 100 bacterial isolates were collected from clinical samples from different hospitals in Isfahan, central of Iran. Of 100 samples of bloodstream, urine, cerebrospinal fluid (CSF), wound, and trachea, 60 bacteria were identified as A. baumannii. The results showed that 100% of the selected isolates were resistant to cefotaxime, ceftazidime, ciprofloxacin, piperacillin-tazobactam, and meropenem. Based on the antibiotic resistance pattern, 25 isolates were chosen for PCR analysis targeting bla OXA−51, bla OXA−23, blaOXA−58, bla NDM, bla IMP, and bla VIM genes PCR results revealed that among the selected isolates, 15 (60.0%) harbored the bla OXA−23 gene, 23 (92.0%) contained the bla OXA−51 gene, and 1 (4.0%) isolate carried the bla NDM gene. Based on MLST analysis, two colistin-resistant Acinetobacter baumannii isolates were categorized as ST2. The ST2 clone represents the predominant sequence type within the CC2 or international clone two. The results showed that the best antibiotic against isolates was colistin. bla OXA−51 and bla OXA−23 genes (oxacillinase genes) were dominant genes, but bla IMP and bla OXA−58 were not local carbapenem resistant genes in Isfahan.